Simultaneous Detection and Typing of Influenza Viruses A and B by a Nested Reverse Transcription-PCR: Comparison to Virus Isolation and Antigen Detection by Immunofluorescence and Optical Immunoassay (FLU OIA) - Herrmann, Björn (American Society for Microbiology, 2001)
A nested reverse transcription (RT)-PCR was developed for simultaneous detection and typing of influenza viruses A and B. The detection limit for influenza virus A subtypes H1 and H3 and that for influenza virus B were between 1 and 4 target gene copies per reaction for each type. The clinical benefit of the RT-PCR method was evaluated by comparing the results with virus isolation and direct immunofluorescence (IF) assays on 215 nasopharyngeal aspirates from patients with suspected influenza virus infection. The RT-PCR detected 83 cases of influenza A, compared to 66 cases detected by virus isolation and 68 cases detected by IF assay. The corresponding figures for the detection of influenza B were 15, 12, and 11 cases, respectively. In total, 16 out of 98 RT-PCR-positive specimens were negative by virus isolation and IF. An optical immunoassay for rapid detection of influenza A and B (FLU OIA; Bio Star Inc., Boulder, Colo.) was compared to RT-PCR and IF on 105 nasopharyngeal aspirates and 79 swabs. The sensitivity for the OIA was 40.4% compared to PCR and 48.8% compared to IF assay, when nasopharyngeal aspirates were examined. The specificities were 94.3 and 93.9%, respectively. The sensitivity was higher for OIA on nasopharyngeal swabs, 77.5% and 86.6% compared to PCR and IF, respectively, while the specificity was lower, 82.0% and 75.5%, respectively. The RT-PCR provides a sensitive and specific method for detecting and typing influenza viruses A and B. The rapid OIA is useful as a complementary test, but it cannot replace established methods without further evaluation.